2015
DOI: 10.3164/jcbn.15-15
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polyphenols increase fecal mucin and immunoglobulin A and ameliorate the disturbance in gut microbiota caused by a high fat diet

Abstract: The effects of dietary polyphenols on human health have mainly been discussed in the context of preventing degenerative diseases, particularly cardiovascular diseases and cancer. The antioxidant properties of polyphenols have been widely studied, but it has become clear that the mechanism of action of polyphenols extends beyond the modulation of oxidative stress, as they are poorly absorbed from the digestive tract. The purpose of this study was to clarify the effects of polyphenols on the colonic environment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 18 publications
2
57
0
1
Order By: Relevance
“…It remains the focus of intense investigation. Taira et al (47) reported that some dietary polyphenols markedly elevated the amount of fecal mucin, suggesting that polyphenol-mediated induction of Akkermansia might result from the mucin production-promoting effects.…”
Section: Discussionmentioning
confidence: 99%
“…It remains the focus of intense investigation. Taira et al (47) reported that some dietary polyphenols markedly elevated the amount of fecal mucin, suggesting that polyphenol-mediated induction of Akkermansia might result from the mucin production-promoting effects.…”
Section: Discussionmentioning
confidence: 99%
“…transresveratrol [103]) have been used extensively. Often, such studies demonstrate that the test substance or (poly)phenol-rich commodity modulate the composition of the gut microbiota and / or ameliorate the harmful effects of the test animal's less than ideal diet [101][102][103][104][105][106][107][108].…”
Section: Prebiotic Effectsmentioning
confidence: 99%
“…The gut microbiota is also an important gut environment factor, and the effects of dietary nutrition on the intestinal barriers' function and gut microbiota have been studied. Dietary fiber and some polyphenolic components have been reported to increase the concentrations of intestinal IgA and mucin and to improve the gut barrier function [4,5] with yogurt, one of the famous fermented foods, influencing the intestinal microbiota [6].…”
Section: Introductionmentioning
confidence: 99%